Transforming Higher Education Through Sustainability and Environmental Education - Terry Link (Issues in Science and Technology Librarianship)
Current concerns over the sustainability of our biosphere for future generations of humans are being scrutinized on the fringes of the higher education complex. What role does higher education play in creating a more sustainable future? What responsibility do librarians have for the current decline in biological systems around the globe? How might we rethink what we do and how we do it? And where do libraries, which were once considered the heart of the university, fit into these questions? I will argue that the situation is potentially critical, that our responsibilities are substantial, and that our chance to show leadership is ripe.